A Pilot Plant Study of Coal Dryer: Simulation and Experiment - Abdul Halim; Afninda Aryuni Widyanti; Celvin Dicky Wahyudi; Fahimah Martak; Eka Luthfi Septiani (ASEAN Journal of Chemical Engineering, 2022)
High moisture content in low-range coal causes low calorific value.  To increase the quality, drying by a coal dryer to minimize moisture content is proposed.  Here, a case study of a cyclone-like conical tube coal dryer pilot plant was reported.  Drying heating uses combustion heat generated from volatile matter combustion.  This approach will solve the two problems simultaneously: decreasing moisture content and volatile matter.  The computational fluid dynamic (CFD) approach is used to study fluid dynamics inside the coal dryer using ANSYS Fluent 2020R2 software.  The CFD simulation results represent the phenomenon of coal drying inside the coal dryer validated by the pilot plant experimental result.  The simulation was carried out in steady and unsteady conditions to understand the drying phenomena.  The simulation firmly fits the experimental result, especially in an unsteady state system, indicating that the simulation result is promising for further coal dryer design.  The optimal condition produces a high moisture content reduction of 86.37%, uniform fluid distribution, and significant volatile matter combustion